Emotional intelligence and career adaptability in employees - Djudiyah; Indrayati, Nafia Kusuma; Fatimatuzzahrah, Siti; Anwar, Zainul (University of Muhammadiyah Malang, 2026)
The era of globalisation and the rapid advancement of information technology have led to the diversification of occupations, resulting in a high level of job uncertainty. This condition has triggered changes in work demands, requiring employees to be flexible in responding to these changes. Employees who can adapt to their job responsibilities tend to be more flexible in adjusting to career demands. This study aims to examine the role of emotional intelligence in employees’ career adaptability. The research subjects were 113 employees working in the service sector, selected using an accidental sampling technique. The instruments used in this study were the Assessing Emotions Scale (AES) and the Career Adapt-Abilities Scale (CAAS–International Form). The data were analysed using simple linear regression and multiple regression analysis. The results indicated that emotional intelligence had a significant effect on employees’ career adaptability. Emotional intelligence contributed 3.8% to career adaptability. The emotional intelligence dimension that had the strongest influence on career adaptability was the ability to manage others’ emotions, followed by the ability to manage or use emotions, emotion perception, and the ability to manage one’s own feelings.